2013 International Conference on Social Computing 2013
DOI: 10.1109/socialcom.2013.117
|View full text |Cite
|
Sign up to set email alerts
|

FinancialCloud: Open Cloud Framework of Derivative Pricing

Abstract: Predicting prices and risk measures of assets and derivatives and rating of financial products have been studied and widely used by financial institutions and individual investors. In contrast to the centralized and oligopoly nature of the existing financial information services, in this paper, we advocate the notion of a FinancialCloud, i.e., an open distributed framework based cloud computing architecture to host modularize financial services such that these modularized financial services may easily be integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Prior to presenting the proposed taxonomy, it is worthy to mention that the identification of elements and components of the categorization used is based on the critical review of key literatures in [40][41][42][43][44][45], the preceding section and subsequent sections. This critical review followed the systematic approach proposed by [52]. Some of these studies include standards and proposal documents from academia and industry as well as independent quantitative and qualitative studies conducted by author.…”
Section: Classification Methodologymentioning
confidence: 99%
“…Prior to presenting the proposed taxonomy, it is worthy to mention that the identification of elements and components of the categorization used is based on the critical review of key literatures in [40][41][42][43][44][45], the preceding section and subsequent sections. This critical review followed the systematic approach proposed by [52]. Some of these studies include standards and proposal documents from academia and industry as well as independent quantitative and qualitative studies conducted by author.…”
Section: Classification Methodologymentioning
confidence: 99%
“…The massive growth is been observed in case of software as a service scenarios. Thus the evaluation of healthcare as a service as demonstrated by A. K. Jha et al [3] and also finance as a service as demonstrated by H. T. Peng et al [4] showcased the modernization of the regular software on cloud away from the contemporary usages. Not alone for the business or commercial spaces, the benefits have also reached to the education domain as well.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Health informatics can help medical researchers diagnose challenging diseases and cancers [3]. Financial analytics can ensure accurate and fast simulations to be available for investors [4]. Education as a Service improves the quality of education and delivery [5].…”
Section: Introductionmentioning
confidence: 99%